SYSTEMATIC LITERATURE REVIEW: PERAN PENERAPAN SIMKAH (SISTEM INFORMASI MANAJEMEN NIKAH) TERHADAP KUALITAS PELAYANAN PUBLIK DI KUA - Wibowo, Sandi Kaci; Bahtiar, Apud Salehudin; Rahmantya, Yanneri Elfa Kiswara (Jurnal Ilmiah Global Education, 2023)
This systematic literature review research explains the application of the marriage management information system (SIMKAH). The presence of an application in marriage data collection called the Marriage Management Information System or SIMKAH which has begun to be applied in various religious affairs offices (KUA). This system is useful for collecting all marriage data from every KUA in Indonesia online and offline, data stored in KUA (in the form of files), ministries of religion (soft files), ministries of home affairs (population data), ministries of finance (financial transaction data). This Marriage Card is an additional proof of document from KUA which has a digital-based bar code, if scanned by a married couple, complete information data will appear regarding marital status, name, date, photo of the bride and groom, and place of marriage. The results showed that the application of SIMKAH in the Digital Marriage Card service at KUA provides convenience, fast procedures, fast and effective validation. SIMKAH has begun to be used publicly and effectively and in 2018 it can print Digital Marriage Cards so that the bride and groom get two documents after carrying out the marriage contract, namely the marriage book and marriage card. The implementation of programs in this digital era, of course, is very beneficial for the benefit of the community.